Formaç\~ao Econômica do Brasil, de Victor Viana, cem anos depois - Mauro Boianovsky; André Bojikian Calixtre (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– Our goal in this paper is to shed light on a forgotten contribution to Brazilian economic thought, that is Victor Viana's 1922 book Histórico da Formaç\~ao Econômica do Brasil (Brazilian Economic Formation's Timeline). That book never got a second edition, and is rarely referenced among both past and present Brazilian economists Still, it brought out relevant economic development issues - such as protectionism and the political and cultural frameworks necessary for development - and anticipated some ideas that would come up in the Brazilian economic debate about twenty years later. It is argued that Viana applied the liberal economic theory of his time - still under the influence of Adam Smith - to underdeveloped countries as seen from the perspective of the Luso-Brazilian mercantilist colonial system that precede our political independence in 1822.
Keywords: B10; B31; 330; Victor Viana; Brazilian economic thought; liberalism and developmentalism